Assessing psychotic‐like symptoms using the BASC‐2: adolescent, parent and teacher agreement. Issue 4 (24th January 2013) - Nugent, Katie L.; Kline, Emily; Thompson, Elizabeth; Reeves, Gloria; Schiffman, Jason
Abstract: Aim: The aim of the current study was to investigate the psychometric properties of the BASC‐2 (Behavior Assessment System for Children, Second Edition) Atypicality subscale in a sample of adolescents receiving mental health services. Methods: A large sample ( n   =  1916) of adolescents aged 12–20 years (median = 14.7 years) completed the BASC‐2. A parent and teacher also completed the measure for each child. We analyzed internal consistency and interrater reliabilities for the Atypicality subscale, as well as the Depression and Hyperactivity subscales for comparison. Further analyses explored the influence of a participant's subscale scores, gender, and quality of relationships with adults on interrater agreement. Results: All subscales demonstrated good internal consistency; however, interrater agreement was low for all subscales. Gender, Atypicality subscale score, and self‐reported quality of relationships with adults could not account for poor interrater agreement. Conclusions: The Atypicality subscale has strong internal consistency across informants. Low interrater agreement for the Atypicality subscale, as well as other scales, however, presents a challenge when interpreting multi‐informant scales.